1992
DOI: 10.1192/bjp.160.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Tardive Dyskinesia

Abstract: Of 113 patients in long-stay wards of a psychiatric hospital, 43 had TD. Twenty-six of the 39 patients who consented to take part in the study were unaware of abnormal involuntary movements. These patients scored significantly lower on a short test of cognitive function than patients who were aware of such movements. The diagnosis of schizophrenia, particularly the 'defect' state with cognitive deficit and negative symptoms, was found to be associated with lack of awareness of TD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Furthermore, antipsychotics are increasingly used for other indications as SGAs have strong mood stabilizing properties which will increase the absolute numbers of drug-induced movement disorders. Fourth, most patients with schizophrenia do not complain of their movement disorder [65][67]. Unawareness of movement disorder and subsequent lack of subjective complaints is a risk factor for diagnostic delay [66].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antipsychotics are increasingly used for other indications as SGAs have strong mood stabilizing properties which will increase the absolute numbers of drug-induced movement disorders. Fourth, most patients with schizophrenia do not complain of their movement disorder [65][67]. Unawareness of movement disorder and subsequent lack of subjective complaints is a risk factor for diagnostic delay [66].…”
Section: Discussionmentioning
confidence: 99%
“…However, this reduced the ability to demonstrate superiority compared to placebo on patient-rated outcomes may have to do with the fact that not all patients are fully aware of the presence or impact of the TD. 75 79 In this context, data are missing that put the efficacy results into the context of patient awareness and burden caused by the TD, such as in subgroup analyses. To comprehensively assess the impact of TD and of treatments for TD, the field will have to define TD-specific rating scales that tap into the subjective and functional relevance of TD that may not necessarily be directly related to total TD severity, but also (rather) to local body area distribution and the functional impact of the abnormal involuntary movements.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports that patients were indifferent to TD were based on older patients with chronic illnesses confined to institutions who were limited by psychosis and negative symptoms and impoverished by cognitive impairments, lack of insight, denial, and few opportunities for social engagement. While up to two thirds of these patients seemed unaware of TD movements, others admitted to being embarrassed by them 3537. By contrast, a recent survey of outpatients with possible TD revealed that 70%–80% were aware of their movements and 50%–60% felt self-conscious or embarrassed by them 20…”
Section: Seriousness and Impact Of Tdmentioning
confidence: 97%